Internet use and rural-urban mental health inequalities: Evidence from China - Nie, Weihao; Hu, Mingzheng; Ye, Xin (Frontiers in Public Health, 2023)
In the context of the new digital era, clarifying the relationship between Internet use and urban and rural residents’ mental health is of important value for reducing rural-urban health inequali-ties. Based on the data of the China Family Panel Studies (CFPS) in 2020, we firstly examined the existence and specific manifestation of mental health inequalities between urban and rural resi-dents. Secondly, we examined the mediating effect of Internet use by the Bootstrap mediating effect measure. Finally, we verified the robustness of the mediating effect. Results showed that mental health inequalities between urban and rural residents objectively did exist, and the use of the Internet played a positive mediation effect on the formation of mental health inequalities between urban and rural areas.